Synthesis And Properties Of Highly Cross-Linked Polysiloxane For Led Encapsulant - Looi , Yien Tyng (2012)

(untitled)
The research focuses on the synthesis of two series of polysiloxane. The first series (S1) is hydrosilyl-terminated polydimethylsiloxane (HTP) that was cured with 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl cyclotetrasiloxane (D4V) and second series (S2) is the incorporation of octaphenylcyclotetrasiloxane (P4) into first series. The polymers of both series underwent thermal curing. UV curing was performed on the first series to improve the curing time as well as comparing their properties. The polysiloxanes product was a water clear gel form. The elastomeric feature of series S1 was dependent on the end-capper concentration, 1,1,3,3- tetramethyldisiloxane while series S2 was dependent on the amount of phenyl group of octaphenylcyclotetrasiloxane (P4) employed during its synthesis. FTIR and NMR was used to confirm the functional group of HTP and completion of the hydrosilylation reaction. TGA was used to measure the residue mass of samples S1 and S2, while DSC was used to find the Tg of cross-linked samples. UV transmittance analysis was used to measure the transparency of the samples. Atago refractometer was used to measure the refractive index of the samples. Lastly, the swelling test was used to estimated crosslink density of samples and Shore A durometer was used to measure the hardness of samples. End-capper concentration of 30% (v/w) in first series was found to affect the optimum toughness of the product. The siloxane-based polymer displayed Tg in the range of -110 ºC to -120 ºC and with excellent thermal stability where decomposition temperature was around 600 ºC. The materials also displayed refractive index of 1.4 – 1.5 which is within an acceptable range of application as electronic devices encapsulant. Series 2 shows higher optical, thermal and mechanical properties compared to series 1. These optical, thermal and mechanical properties were closely related to the cross-link density. The effect of fractional free volume and ‘densification’ of the network was elucidated and found to contribute to this dependency. Lorentz-Lorenz model was used to support these observations.